(untitled) (KYAMC Journal, 2013)
Aim: To observe the effects of radiation and concurrent chemo-radiation as treatment on locally advanced oesophageal carcinoma in human. Methods: Randomized prospective study was carried out in the Department of Radiotherapy, Dhaka Medical College and Hospital, Dhaka during the period of July 2001 to June 2002. Patients of locally advanced oesophageal carcinoma, histologically squamous cell carcinoma type was included in the study. After proper evaluation Arm-A was treated by concurrent chemotherapy weekly with Inj. Cisplatinum and Inj. 5-Flurouracil and conventional radiotherapy with a total dose of 44 Gy in 22 fractions in 4.5 weeks. Arm-B was treated by conventional radiotherapy with the same dose as that of Arm-A. Every patient was evaluated by monitoring routinely to see the responses. All the resultant informations were kept preserved on a prescribed data sheet. These informations were than analyzed statistically and results were compiled accordingly. Result: Out of 30 patients in Arm-A, complete desirable response was observed in 21 cases and partial response in 9 cases, where as out of 30 patients in Arm-B it was 13 and 17 cases respectively. Conclusion: Concurrent chemo-radiation showed better response than radiation alone, though toxicities were little bit higher but it was acceptable and easily manageable. DOI: http://dx.doi.org/10.3329/kyamcj.v2i1.13514 KYAMC Journal Vol.2(1) 2011 pp.114-117